2016
DOI: 10.1093/glycob/cww053
|View full text |Cite
|
Sign up to set email alerts
|

Base-modified UDP-sugars reduce cell surface levels of P-selectin glycoprotein 1 (PSGL-1) on IL-1β-stimulated human monocytes

Abstract: P-selectin glycoprotein ligand-1 (PSGL-1, CD162) is a cell-surface glycoprotein that is expressed, either constitutively or inducibly, on all myeloid and lymphoid cell lineages. PSGL-1 is implicated in cell–cell interactions between platelets, leukocytes and endothelial cells, and a key mediator of inflammatory cell recruitment and transmigration into tissues. Here, we have investigated the effects of the β-1,4-galactosyltransferase inhibitor 5-(5-formylthien-2-yl) UDP-Gal (5-FT UDP-Gal, compound 1) and two cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Selectins are difficult structures to create effective small molecule antagonists against. Consequently, several drugs that inhibit the synthesis of PSGL-1 and therefore have the potential to suppress P-selectin-dependent eosinophil recruitment are being examined ( 98 ). These compounds have been reported to inhibit the synthesis of PSGL-1 under inflammatory conditions, rather than affecting expression at resting state, and might therefore provide an important safety benefit of not affecting the necessary immunosurveillance of the host ( 98 ).…”
Section: Pharmacological Strategies For Modulating Platelet–eosinophimentioning
confidence: 99%
See 1 more Smart Citation
“…Selectins are difficult structures to create effective small molecule antagonists against. Consequently, several drugs that inhibit the synthesis of PSGL-1 and therefore have the potential to suppress P-selectin-dependent eosinophil recruitment are being examined ( 98 ). These compounds have been reported to inhibit the synthesis of PSGL-1 under inflammatory conditions, rather than affecting expression at resting state, and might therefore provide an important safety benefit of not affecting the necessary immunosurveillance of the host ( 98 ).…”
Section: Pharmacological Strategies For Modulating Platelet–eosinophimentioning
confidence: 99%
“…Consequently, several drugs that inhibit the synthesis of PSGL-1 and therefore have the potential to suppress P-selectin-dependent eosinophil recruitment are being examined ( 98 ). These compounds have been reported to inhibit the synthesis of PSGL-1 under inflammatory conditions, rather than affecting expression at resting state, and might therefore provide an important safety benefit of not affecting the necessary immunosurveillance of the host ( 98 ). Heparin is known to inhibit P-selectin-dependent events, and a non-anticoagulant form of heparin ( N -acetyl-de- O -sulfated-heparin), has recently been reported to disrupt platelet-dependent eosinophil recruitment in animal models ( 93 ).…”
Section: Pharmacological Strategies For Modulating Platelet–eosinophimentioning
confidence: 99%
“…Thus, an alternative approach is to reduce the cell surface of functional PSGL-1, in particular sLeX. To date, attempts to inhibit the biosynthesis of sLeX have been accomplished by interfering with functional glycosylation sites of sLeX to inhibit galactosylation [34], sialylation [35], and fucosylation [36]. IELLQAR, a peptide analogue of selectin ligands, potently blocks binding to the natural selectin ligand sLeX with substantially high affinity, with an IC 50 value of 10 −5 M [13].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that platelet aggregation was inhibited by the eosinophil cationic protein (ECP) and eosinophil supernatant [55]. The role of eosinophils in platelet aggregation and thrombosis is not yet clear [56]. Certainly there is a therapeutic potential in disrupting eosinophil-platelet interactions in asthmatic patients inhibiting platelet activation and release of platelet cytokines or platelet interaction with other inflammatory cells such as eosinophils.…”
Section: Platelet-eosinophil Interactions In Asthmamentioning
confidence: 99%